Multimodality cardiac computed tomography angiography and magnetic resonance with clinical-grade scanners provide robust assessment of cardiac morphology and function in rabbits - Gitsioudis, Gitsios; Nunninger, Maximilian Martin; Missiou, Anna; Wolf, Peter Georg; Katus, Hugo; Korosoglou, Grigorios (Journal of thoracic disease, 2019)
Background: Non-invasive computer tomography (CT)- and magnetic resonance (MR)-based cardiac imaging still remains challenging in rodents. To investigate the robustness of non-invasive multimodality cardiac imaging in rabbits using clinical-grade CT and MR scanners. - Methods: A total of 16 rabbits (2.7-4.0 kg) serially underwent cardiac-gated imaging using a clinical-grade 256-row CT and a 1.5 Tesla MR-scanner at baseline and at 4-month follow-up (16±1 weeks). Image analysis included image quality (5-grade scale), left ventricular (LV) volumes, LV stroke volume, LV diameters, LV wall thickness and ejection fraction (LVEF). - Results: Cardiac MR (CMR) and CT angiography (CTA) provide images with an overall good image quality (excellent or good quality: CMR 82% vs. CTA 78%, P=0.68). Linear regression analysis demonstrated a good correlation of all diameters (diam.) and volumes (vol.) as assessed by CTA and CMR (diam.: r=0.9, 95% CI: 0.8-0.9; vol.: r=0.8, 95% CI: 0.6-0.9; P Conclusions: Multimodality non-invasive assessment of cardiac function and aortic hemodynamics is feasible and robust in rabbits using clinical-grade and MR and CT scanners. These imaging modalities could improve serial cardiac assessment for disease monitoring in preclinical settings.